Co-Active Life Coaching as a Treatment for Adults with Obesity - Courtney Newnham-Kanas; Jennifer D. Irwin; Don Morrow (International Journal of Evidence Based Coaching and Mentoring, 2008)
This study evaluates the impact of one-on-one coaching on the waist circumference, BMI, self-esteem, self-efficacy, physical activity, and functional health status of adults with obesity. A one-group withinsubjects, pre-test post-test study design was used. The study took place at the University of Western Ontario from June-October 2007. A total of 20 men and women aged 35-55, with a BMI ≥ 30 participated in the study. Each engaged in six to eight 35-minute sessions with a Certified Professional Co-Active Coach during which they explored desired changes and how to achieve them. Paired t-tests were used to analyse the pre- and post-quantitative data and inductive content analysis was used to assess the qualitative interviews. Significant decreases in waist circumference and increases in self-esteem and functional health status were found. Qualitatively, participants reported an increase in daily physical activity and healthier dietary choices, feelings of optimism, and greater self-acceptance. Thus life coaching shows promise as an obesity intervention, although more research is needed.